EFFORTS TO IMPROVE THE QUALITY OF PRISONERS THROUGH LEARNING IN SURAKARTA CLASS I DETENTION CENTER - Ardian Rizky Putranto; Herry F Butar Butar; Muhammad Ali Equatora; Imaduddin Hamzah (Universitas Nusa Cendana, 2026)
This study analyzes efforts to improve the quality of inmates through educational programs implemented at the Class I Detention Center (Rutan) Surakarta. The research is based on the principle that education is a fundamental right for all citizens, including inmates, and plays a key role in supporting their rehabilitation and reintegration into society. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings show that the institution has implemented various formal and non-formal education programs, including package education (levels A, B, and C), skills training, as well as personality and independence development activities. These programs contribute significantly to character building, skill enhancement, and preparing inmates for life after release. However, the implementation of these programs faces several challenges, particularly limited facilities and infrastructure, as well as a shortage of supporting human resources. Despite these constraints, collaboration between correctional officers, inmates, and external partners has enabled the programs to run effectively and provide tangible benefits, including improved self-reliance and reduced tendencies toward reoffending. In conclusion, educational programs in correctional institutions play a crucial role in inmate development. It is recommended that the institution continue to innovate in learning methods and strengthen partnerships with stakeholders to ensure the sustainability and effectiveness of rehabilitation programs. Keywords: Inmate Quality Improvement; Educational Program; Social Reintegration